The Impact Of Information Systems, Work Flexibility On Employee Performance: Systematic Literature Review - intan dwi sulistyowati, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract Literature research is the process of finding out as well as studying research findings that have been published by researchers related to previous scientific work. Literature research can help improve your knowledge of current research topics. To make a good and proper literature review, recent research and relevant research findings are very important. Theories, concepts, and phenomena related to variable formation can be corroborated by previous research and relevant research. In this article, the results of evaluating the various components that can affect business performance are presented. Having realized how important it is to improve employee performance in private banking institutions, we must find the things that can affect it. Previous studies have shown that the use of information systems and work flexibility, especially in the financial sector, can improve employee performance. The purpose of this theoretical review is to investigate the effects of information systems and work flexibility in private banking. Another objective is to gain a better understanding of some of the indicators involved in these variables, which can be used as a reference for future research. According to information systems research, work flexibility affects employee performance.